Large-scale high-numerical-aperture super-oscillatory lens fabricated by direct laser writing lithography. Issue 36 (4th June 2018) - Ni, Haibin; Yuan, Guanghui; Sun, Liangdong; Chang, Ning; Zhang, Di; Chen, Ruipeng; Jiang, Liyong; Chen, Hongyuan; Gu, Zhongze; Zhao, Xiangwei
Abstract : Super-oscillatory lens achieving sub-Abbe–Rayleigh diffraction limit focusing in the optical far-field were produced by direct laser writing (DLW) lithography method. Abstract : In this study, direct laser writing (DLW) lithography is employed to fabricate a large-scale and high-numerical-aperture super-oscillatory lens (SOL), which is capable of achieving a sub-Abbe–Rayleigh diffraction limit focus in the optical far-field region by delicate interference. Large-diameter (600 μm), amplitude-modulated and phase-type SOLs with the smallest annular ring width of 1 μm are fabricated, and they have high quality. The dependence of DLW printing on the fabrication parameters including substrate materials, laser power, and scanning speed is well investigated. A standard procedure to manufacture high-quality binary amplitude SOLs is presented, which avoids direct printing patterns on metal films and reduces the surface roughness dramatically. Random displacements between squares constituting SOLs are discussed, and their influence on the focusing performance is studied by both numerical simulations and experiments. The optical performances of the SOLs fabricated by the DLW method are experimentally characterized, and a needle-like focus with a spot size of 0.42 λ and a depth of focus of ∼6 μm are confirmed at a working distance of 100 μm for λ = 633 nm, thus giving an effective numerical aperture as high as 1.19 in air. As a complementary sub-micrometer fabrication method between traditional lithography and nanofabrication method, DLW is proved to be a promising approach to manufacture SOLs, presenting advantages of relatively high speed, low equipment volume, less complexity and sub-micrometer lateral resolution. Such SOLs can be very useful in high resolution bio-imaging on rough surfaces and in the related research fields.